1937
DOI: 10.1002/hlca.193702001166
|View full text |Cite
|
Sign up to set email alerts
|

Synthesen niederer Methyl‐zucker

Abstract: form6 par reaction entre 1 moI6cule d'anhydride malkique et une molGcule d'ozone.Deux des essais ont donne respectivement comme aldPhydit6 3,5 et 4 millimol. gr.Un essai a donne comme acidite 4,s millimol. gr. Les chiffres obtenus pour l'aldChydit6 e t I'aciditB doivent dtre trop faibles, car l'ozonide (qui s'est quelquefois sBpar6 sous forme d'une neige blanche) ou sit solution a subi partiellement une decomposition spontanee, dBgageant un gaz dans lequel nous avons reconnyde l'osyde de carbone et du gaz carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

1939
1939
1995
1995

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 3 publications
1
14
0
Order By: Relevance
“…The mechanism shown in figure 1 is consistent with the early theoretical considerations which led to the postulate that the aldolasetype reaction is catalyzed both by a Schiff base (49)(50)(51) and by a base catalyst (2,(18)(19)(20)(21). It is interesting to compare this mechanism with the results reported by Westheimer and Cohen (50), who found that an aldol cleavage was catalyzed by an amine (thought to form a Schiff base complex) together with hydroxide ion.…”
Section: B Mechanism Of Actionsupporting
confidence: 86%
“…The mechanism shown in figure 1 is consistent with the early theoretical considerations which led to the postulate that the aldolasetype reaction is catalyzed both by a Schiff base (49)(50)(51) and by a base catalyst (2,(18)(19)(20)(21). It is interesting to compare this mechanism with the results reported by Westheimer and Cohen (50), who found that an aldol cleavage was catalyzed by an amine (thought to form a Schiff base complex) together with hydroxide ion.…”
Section: B Mechanism Of Actionsupporting
confidence: 86%
“…6,7-dimethyl-8-ribityllumazine and 5-amino-6-ribitylamino-2,4(1H,3H)-pyrimidinedione were synthesized as described (10). 3,4-dihydroxy-2-butanone was synthesized from acetol and formaldehyde under previously described conditions (11). Restriction enzymes and DNA modification enzymes were from Pharmacia Biotech Inc., New England Biolabs, or Boehringer Mannheim.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent deveolpment on the total synthesis of optically active natural products, 1.2-isopropylidene 1 D-glyceraldehyde (1) has been used as a chiral synthon for s number of biolodcal active compounds 5 6 such as prostaglandins2, brefeldin A~, ipsdieno14, prestalotin and leukotriene A 4 . We have shown, in a previous paper7, 3(S)-[ 3-hydroxy-1(E)-propylenyllcyc10pentanone (2) derived from 1 was a potential intermediate leading to antirhine and brefeldin A In our continuous efforts on the synthesis of natural products, secologanin and sesquiterpene lactones, we required a synthesis of the y-butyrolactone possessing an appropriate substituent at C3 and C4.…”
mentioning
confidence: 99%